META-ANALYSIS OF LITERATURE REVIEW (2020–2025): THE ROLE OF SPECIAL EDUCATION TEACHERS IN THE LITERACY OF STUDENTS WITH HEARING IMPAIRED (SEN-HI) THROUGH MALAYSIAN SIGN LANGUAGE AND DIGITAL COMPETENCE - Abdul Rahman , Nur’Hamizah; Piragasam, Grace Annamal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study takes the form of a meta-analytic literature review that evaluates the role of special education teachers in strengthening the literacy development of students with hearing impaired (SEN-HI) through mastery of sign language and digital competence. A total of 35 articles published between 2020 and 2025 were systematically analyzed using both qualitative thematic and quantitative descriptive approaches. The analysis revealed three main themes: (i) special education teachers as mediators of language and culture; (ii) teachers’ digital competence as a catalyst for literacy achievement; and (iii) structural challenges, professional training, and educational policy support. Global findings indicate that the systematic integration of sign language with formal literacy instruction, together with the use of digital technology supported by continuous professional development, enhances the literacy achievement of deaf students. However, in the Malaysian context, the literacy gap remains significant due to a shortage of teachers proficient in Malaysian Sign Language (BIM), limited bilingual learning materials, and unequal digital infrastructure. This study emphasizes the need for holistic strategies that involve professional training, the development of bilingual-bicultural literacy modules, and the strengthening of inclusive education policies to empower the literacy development of students with hearing impaired (SEN-HI).